Comparative Genomics of the Baltic Sea Toxic Cyanobacteria Nodularia spumigena UHCC 0039 and Its Response to Varying Salinity - Teikari, Jonna E.; Hou, Shengwei; Wahlsten, Matti; Hess, Wolfgang R.; Sivonen, Kaarina (Frontiers in Microbiology, 2018)
Salinity is an important abiotic factor controlling the distribution and abundance of Nodularia spumigena, the dominating diazotrophic and toxic phototroph, in the brackish water cyanobacterial blooms of the Baltic Sea. To expand the available genomic information for brackish water cyanobacteria, we sequenced the isolate Nodularia spumigena UHCC 0039 using an Illumina-SMRT hybrid sequencing approach, revealing a chromosome of 5,294,286 base pairs (bp) and a single plasmid of 92,326 bp. Comparative genomics in Nostocales showed pronounced genetic similarity among Nodularia spumigena strains evidencing their short evolutionary history. The studied Baltic Sea strains share similar sets of CRISPR-Cas cassettes and a higher number of insertion sequence (IS) elements compared to Nodularia spumigena CENA596 isolated from a shrimp production pond in Brazil. Nodularia spumigena UHCC 0039 proliferated similarly at three tested salinities, whereas the lack of salt inhibited its growth and triggered transcriptome remodeling, including the up-regulation of five sigma factors and the down-regulation of two other sigma factors, one of which is specific for strain UHCC 0039. Down-regulated genes additionally included a large genetic region for the synthesis of two yet unidentified natural products. Our results indicate a remarkable plasticity of the Nodularia salinity acclimation, and thus salinity strongly impacts the intensity and distribution of cyanobacterial blooms in the Baltic Sea.